Factors shaping subjective financial well-being in emerging adults: A comparative study of Italy and Germany - Maria Rosa Miccoli; Yury Shevchenko; Paola Iannello; Ulf-Dietrich Reips (PLoS ONE, 2025)
Academics and policymakers recognize the growing importance of subjective financial well-being for emerging adults, yet little is known about the factors influencing the subjective financial well-being perceived by the emerging adult population. We aim to investigate the role of socio-demographic characteristics (job type, age, country of residence), individual differences in financial knowledge (financial literacy), skills (financial behavior), cognitive response styles (impulsiveness, future orientation, and maximization), and attitudinal components (trust in governmental institutions and financial professionals) in shaping subjective financial well-being among emerging adults in Italy and Germany, representing the Mediterranean and Northern models of the transitions to adulthood, respectively. A sample of 385 participants residing in Italy (n =  193) and Germany (n =  192) voluntarily participated in an online survey. Variables such as trust and maximization were incorporated into a prior financial well-being model to assess their relevance in predicting subjective financial well-being. In Model 1, variables from the prior theoretical model (socio-demographic characteristics, financial literacy, financial behavior, impulsiveness, and future orientation) were analyzed. In Model 2, trust and maximization were added as predictors of subjective financial well-being. Results revealed that the inclusion of these variables improved the model fit, and further confirmed the significant role of age, financial behavior (specifically, caring for financial matters), impulsiveness, future orientation, and trust in governmental institutions in subjective financial well-being.